HUBUNGAN PENDIDIKAN DENGAN MASYARAKAT DALAM PERSPEKTIF SOSIOLOGI - ISKANDI, ISKANDI (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2020)
Education and society have a very strong reciprocal relationship. This reciprocal relationship can be explained philosophically and sociologically by looking at each other's roles, and can also be explained by pedagogies. Community stratification has a role that influences the educational process, then education itself has a role and influence on the community stratification system. So basically, education and community stratification systems have an integral relationship with each other, the community is a unitary system that is interdependent and education-related is required to make continuous adjustments to the development of society. In accordance with the characteristics of the community, the education chosen by the community is education that can provide technological, functional, individual, informative and open capabilities.